DOSE-RATE EFFECT OF RADIATION ON RAT MAMMARY CARCINOGENESIS AND AN EMERGING ROLE FOR STEM CELL BIOLOGY. Issue 13 (9th September 2022) - Imaoka, Tatsuhiko; Nishimura, Mayumi; Daino, Kazuhiro; Hosoki, Ayaka; Kudo, Ken-ichi; Iizuka, Daisuke; Nagata, Kento; Takabatake, Masaru; Nishimura, Yukiko; Kokubo, Toshiaki; Morioka, Takamitsu; Doi, Kazutaka; et al.
Abstract: The uncertain cancer risk of protracted radiation exposure at low dose rates is an important issue in radiological protection. Tissue stem/progenitor cells are a supposed origin of cancer and may contribute to the dose-rate effect on carcinogenesis. The authors have shown that female rats subjected to continuous whole body γ irradiation as juveniles or young adults have a notably reduced incidence of mammary cancer as compared with those irradiated acutely. Experiments using the mammosphere formation assay suggested the presence of radioresistant progenitor cells. Cell sorting indicated that basal progenitor cells in rat mammary gland were more resistant than luminal progenitors to killing by acute radiation, especially at high doses. Thus, the evidence indicates a cell-type-dependent inactivation of mammary cells that manifests only at high acute doses, implying a link to the observed dose-rate effect on carcinogenesis.